2021
DOI: 10.3390/beverages7030050
|View full text |Cite
|
Sign up to set email alerts
|

Towards Accelerated Autolysis? Dynamics of Phenolics, Proteins, Amino Acids and Lipids in Response to Novel Treatments and during Ageing of Sparkling Wine

Abstract: Premium sparkling wine produced by the traditional method (analogous to the French méthode champenoise) is characterised by the development of aged wine character as a result of a second fermentation in the bottle with lees contact and lengthy ageing. Treatments (microwave, ultrasound, or β-glucanase enzymes) were applied to disrupt the cell wall of Saccharomyces cerevisiae and added to the tirage liquor for the second fermentation of Chardonnay-Pinot Noir base wine cuvée and compared to a control, to assess e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…During extended ageing, the free amino nitrogen content tends to decrease, potentially due to the breakage reactions of amino acids (deamination) or the formation of other compounds [49]. Our results are in agreement with the findings of Gnoinski et al [45] for Chardonnay and Pinot noir sparkling wines, when yeasts subjected to different lysis treatments were added to the TL during the second fermentation, revealing that these enzymes represent tools that could potentially be used to induce the release of yeast compounds into the wine. In contrast, we found that yeast walls produced the lowest levels of free amino nitrogen (Table 2).…”
Section: Total Polysaccharides Total Proteins and Free Amino Nitrogensupporting
confidence: 93%
See 2 more Smart Citations
“…During extended ageing, the free amino nitrogen content tends to decrease, potentially due to the breakage reactions of amino acids (deamination) or the formation of other compounds [49]. Our results are in agreement with the findings of Gnoinski et al [45] for Chardonnay and Pinot noir sparkling wines, when yeasts subjected to different lysis treatments were added to the TL during the second fermentation, revealing that these enzymes represent tools that could potentially be used to induce the release of yeast compounds into the wine. In contrast, we found that yeast walls produced the lowest levels of free amino nitrogen (Table 2).…”
Section: Total Polysaccharides Total Proteins and Free Amino Nitrogensupporting
confidence: 93%
“…Total protein concentration did not show statistically significant differences between the control and the treated wines (Table 2). In agreement with the results of Gnoinski et al [45], the only factor that shows statistically significant differences is ageing time, showing a significant increase (Table 2). However, Gnoinski et al's findings said that this increase stopped at 12 months of ageing, whereas our results reveal a continuous increase throughout the ageing process up to the 21 months under study, similar to what happened in our previous study with short ageing [28].…”
Section: Total Polysaccharides Total Proteins and Free Amino Nitrogensupporting
confidence: 92%
See 1 more Smart Citation
“…The aim of these studies was to enhance the availability of autolytic compounds, including amino acids, peptides, and proteins, among others (Gnoinski et al, 2021a,b). In one study, chemical parameters of phenolics, amino acids, proteins and lipids were monitored at 6-, 12-, and 18-months post-tirage during lees aging, with microwave and β-glucanase enzyme treatments showing a 10% increase in total free amino acids at 18-months compared to the control (bottle-aged on lees) and ultrasound conditions (Gnoinski et al, 2021a). Future research related to the implications of increased amino acid availability on the Maillard reaction during sur-lies aging, and possible impacts on accelerated Maillard chemistry when treating the sparkling wine matrix with high-energy ultrasound or microwave is necessary.…”
Section: Accelerated Autolysismentioning
confidence: 99%
“…Cysteine produced more than 400 distinct Maillard reaction products, despite it being considered a relatively unreactive amino acid in the Maillard reaction (Hemmler et al, 2018), although it has been studied in the context of the Maillard reaction in model sparkling wines (Pripis-Nicolau et al, 2000;Marchand et al, 2011). Cysteine is reported to be found in red wine at concentrations of approximately 1-6 mg/l (Pripis-Nicolau et al, 2001), although it was reported to be below 0.1 mg/l in traditional method sparkling wine aged on lees (63% chardonnay, 37% pinot noir; fermented with S. cerevisiae IOC 18-2007;Gnoinski et al, 2021a).…”
Section: Amino Acid Structure and Maillard Reactivitymentioning
confidence: 99%